PENINGKATAN KETERAMPILAN MENULIS TEKS PROSEDUR BERDASARKAN PROFESI DENGAN PENDEKATAN DIFERENSIASI DI SMPN 12 MALANG - Gandesswari, Arim; Rahutami; Suwanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Observations revealed that students struggled with writing procedural texts. This study aimed to improve students' writing skills in procedural text lessons through a differentiated approach. It employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles with 32 participating students. Data were gathered through diagnostic assessments, observations, documentation, and writing skill test results. Data analysis involved quantitative and qualitative descriptive methods, comparing results from the pre-cycle, Cycle I, and Cycle II. The findings indicate that implementing product differentiation offering media choices such as posters, infographics, videos, and presentationseffectively improved students' procedural text writing skills. Learning mastery increased from 20.83% in the pre-cycle to 87.50% in Cycle I, reaching 100% in Cycle II. The students' average score also rose from 79.44 in Cycle I to 87.09 in Cycle II. The results demonstrate significant improvements in students' scores, active participation, and learning interest.